Chinese culture and cancer among Malaysian chinese cancer survivors - Yew, Wong Chin Vivien; Mohd Noor, Noor Azlan (Canadian Center of Science and Education, 2013)
We conduct a case study on cancer survivors with the aim to investigate the influence of specific social and cultural factors that may have influenced informants’ unhealthy lifestyle and health-seeking behaviour and thus causing the illness - cancer. In the 50 in-depth interviews with 50 informants, this report of Chinese culture and cancer was designed to evaluate the role of Chinese culture in causing cancer. In its discussion section, this report focuses on three main themes of cancer diagnosis among the informants: (i) perception of health and illness after cancer, (ii) emotional effects of stress in cancer etiology, and (iii) decision-making and cancer treatment. In summary, several Chinese sociocultural beliefs and practices played their roles in the informants’ ways of living, health-seeking behaviours, and cancer diagnosis. The results suggested that Chinese cultural beliefs and practices influenced the Malaysian Chinese cancer survivors’ perceptions of health, illness, and cancer treatment.